2020
DOI: 10.1590/1983-1447.2020.20190025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between emotional states before cardiac valve surgeries with postoperative complications

Abstract: Objective: To investigate associations between preoperative anxiety and depression symptoms and postoperative complications and the sociodemographic and clinical characteristics of patients undergoing valve repair surgery. Method: Observational, exploratory and prospective study. The consecutive non-probabilistic sample consisted of patients undergoing their first valve repair surgery. Data were collected from September 2013 to September 2015, in a university hospital in the interior of São Paulo, Brazil. Sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…In this context, patients awaiting cardiac surgery may experience high levels of anxiety symptoms, due to fears, concerns and uncertainties about the surgery. Studies have shown that anxiety symptoms have influenced patients’ recovery in the postoperative period (PO) of cardiac surgeries, in addition to potentiating the occurrence of complications, increasing hospital stay, decreasing the effectiveness of cardiac rehabilitation programs and increasing postoperative mortality ( 5 - 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, patients awaiting cardiac surgery may experience high levels of anxiety symptoms, due to fears, concerns and uncertainties about the surgery. Studies have shown that anxiety symptoms have influenced patients’ recovery in the postoperative period (PO) of cardiac surgeries, in addition to potentiating the occurrence of complications, increasing hospital stay, decreasing the effectiveness of cardiac rehabilitation programs and increasing postoperative mortality ( 5 - 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…A ansiedade dos sujeitos se reflete principalmente em preocupações acerca do medo da morte, local a ser operado, complicações no pós-operatório e dor sentida, anestesia, entre outros. (Rodrigues et al, 2020;Peng et al, 2020;Reynaud et al, 2021;Felix et al, 2018;Garcia et al, 2018;Mudgalkar et al, 2022;Medina-Garzó, 2019;Gu et al, 2021).…”
Section: Eixo Temático 1: Reações Emocionais E Comportamentais Eviden...unclassified
“…Diante desse contexto, os pacientes que aguardam a cirurgia cardíaca podem vivenciar altos níveis de sintomas de ansiedade, devido a medos, preocupações e incertezas sobre a cirurgia. Estudos têm demonstrado que sintomas de ansiedade têm influenciado na recuperação do paciente no pós-operatório (PO) de cirurgias cardíacas, além de potencializar a ocorrência de complicações, aumentar o tempo de internação, diminuir a eficácia de programa de reabilitação cardíaca e aumentar a mortalidade pós-operatória (5)(6)(7) .…”
Section: Introductionunclassified